Bifacial and Angular‐Resolved Performance Characterization of Ultrathin Cu(In,Ga)Se2 Solar Cells Including Nanostructures - Tristan Koehler; Yao Gao; Martina Schmid (Advanced Energy & Sustainability Research)
Bifacial solar cells experience growing interest not just for crystalline silicon photovoltaic modules. Thin‐film solar cells deposited on a transparent back contact bring inherent semitransparency, making them ideally suited for bifacial applications. Herein, a systematic investigation of bifacial measurement procedures is performed on semitransparent ultrathin Cu(In,Ga)Se2 (CIGSe) solar cells on transparent conductive oxide, including nanostructures. The measurements are further extended by angular‐resolved performance studies. The bifaciality of the samples is determined to be ≈80% in current and ≈65% in power, and enables the calculation of an equivalent irradiance for solar cell testing under >1 sun front illumination only. The results are compared to bifacial operation, i.e., simultaneous front and rear irradiance, and to the summation of individual front and rear performance measurements up to 1 sun. It is revealed that highly similar results can be obtained for these approaches and that the integration of nanostructures supports device stabilization. Particularly, the higher (75 nm) SiO2 nanomeshes can enable performance enhancement. Furthermore, the angular‐dependent behavior follows the expected trend of reduced illumination intensity according to the cosine of the incident angle. In these findings, the suitability of semitransparent ultrathin CIGSe solar cells for bifacial operation and the benefit of integrated nanostructures is confirmed.